ANALISA PENCEMARAN AIR TANAH BERDASARKAN METODE GEOLISTRIK STUDI KASUS TEMPAT PEMBUANGAN AKHIR SAMPAH MUARA FAJAR KECAMATAN RUMBAI - Juandi M Juandi M (Jurnal Ilmu Lingkungan, 2009)
The reseacrh to analyze pollution of ground water based on Geo-electrical methods cased onMuara Fajar Landfill Kecamatan Rumbai. The result obtained that resistivity value on point 2 atnorth of Muara Fajar Landfill (0,702-8.250 ohm-m), on point 4 at west of landfill (0,144-501.335 ohm-m), on point 3 at south of landfill (0,0103-11588 ohm-m), on point 1 at east oflandfill (0,601-51.294 ohm-m), on point 5 at centre of landfill (0,737-1.468.744 ohm-m). Basedon resistivity value above, all of the points had been polluted by leachet, dominantly at northand west point of landfill cause resistivity value less 10 ohm-m (fresh water). Resistivity valuehad showed that leachet flowed towards centre of landfill then around it and polluted groundwater systems of community around.